2003
DOI: 10.1038/sj.jea.7500262
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between different traffic-related particle indicators: Elemental carbon (EC), PM2.5 mass, and absorbance

Abstract: Here we compare PM 2.5 (particles with aerodynamic diameter less than 2.5 mm) mass and filter absorbance measurements with elemental carbon (EC) concentrations measured in parallel at the same site as well as collocated PM 2.5 and PM 10 (particles with aerodynamic diameter less than 10 mm) mass and absorbance measurements. The data were collected within the Traffic-Related Air Pollution on Childhood Asthma (TRAPCA) study in Germany, The Netherlands and Sweden. The study was designed to assess the health impact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
138
1
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 209 publications
(151 citation statements)
references
References 35 publications
6
138
1
1
Order By: Relevance
“…Because EC is the dominant light-absorbing substance in the atmosphere (Hoek et al, 1997;Horvath et al, 1996;Seinfeld and Pandis, 1998), an alternative way to estimate EC concentrations in the atmosphere as BS is to measure light absorption or reflectance of PM, collected on filter media. Several studies have reported that BS, derived from absorbance coefficients, is well correlated with the concentration of EC or soot and can be recommended as a valid and cheap indicator in studies on combustion-related air pollution and health (Cyrys et al, 2003;Götschi et al, 2002;Janssen et al, 2001;Kinney et al, 2000).…”
Section: Analysis Of Black Smokementioning
confidence: 99%
See 2 more Smart Citations
“…Because EC is the dominant light-absorbing substance in the atmosphere (Hoek et al, 1997;Horvath et al, 1996;Seinfeld and Pandis, 1998), an alternative way to estimate EC concentrations in the atmosphere as BS is to measure light absorption or reflectance of PM, collected on filter media. Several studies have reported that BS, derived from absorbance coefficients, is well correlated with the concentration of EC or soot and can be recommended as a valid and cheap indicator in studies on combustion-related air pollution and health (Cyrys et al, 2003;Götschi et al, 2002;Janssen et al, 2001;Kinney et al, 2000).…”
Section: Analysis Of Black Smokementioning
confidence: 99%
“…In Paper IV the areas studied were the same as those studied in the impact of TrafficRelated Air Pollution on Childhood Asthma (TRAPCA) study (Cyrys et al, 2003;Emenius et al, 2003). They were Norrmalm in Stockholm's city centre, the municipalities of Solna and Sundbyberg located about 10 km NW of the city centre, and the municipality of Järfälla which lies about 25 km NW of the city centre.…”
Section: Spatial Differencesmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, in addition to the measurements of particle number and/or mass concentration the characterization of the chemical composition of particles may also be important for assessment of health effects. Several studies have documented that black smoke (BS), derived from absorbance coefficients, is well correlated with the concentration of elemental carbon (EC) or soot and can be recommended as a valid and cheap indicator in studies on combustion-related air pollution and health (Kinney et al, 2000;Janssen et al, 2001;Gotschi et al, 2002;Cyrys et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…In the United States, the recent emphasis on fine particles (PM 2.5 ) has resulted in attempts to characterize its relationship with traffic. However, comparative studies have shown that the elemental carbon content of PM is a better indicator of traffic than PM mass (Cyrys et al, 2003;Smargiassi et al, 2005), even when measured indoors . There are many other elements and compounds that may also be associated with vehicular traffic (Schauer et al, 2006;Cadle et al, personal communication), most of which are not routinely monitored:…”
Section: Exposures Based On ''Traffic-related'' Ambient Air Qualitymentioning
confidence: 99%